Lifelong citizenship learning: a narrative study of lives - Ana Arraiz Pérez; Verónica Azpillaga Larrea; Fernando Sabirón Sierra (Sociedad Iberoamericana de Pedagogía Social, 2016)
The study has two objectives: to understand the construction of civic identity and draw some key conclusions for the interpretation of its learning as active citizens. The study was carried out through life stories, using a multiple-case design. Three biographical oriented interviews were used to prepare each of the stories. The qualitative handling of the data used dual analysis: sequential analysis, as a reflection of the identity construction processes throughout life, and categorical analysis as a connection between the "what" and the "how" people learn their civic identity. The results of the sequential analysis show life spans that, in their singularity, reflect the constant identification and desire to improve, efficiently, the immediate surroundings where people develop, as well as the continuous practice of social action. The categorical analysis produced an interpretative model split into two interrelated dimensions. On one hand the "learning results" dimension with three macro-categories: "action", defined by the possession of skills (leadership and power, empathy and dialogue, initiative and innovation); "commitment", defined by certain values (vitality and viability, sensitivity and responsibility, regeneration and transformation); and "identity" (situated, discursive and dialectic). On the other hand, the "learning processes" dimension, with the following macro-categories: "scenarios"; "life experiences" and "socialisation. The discussion of results emphasises the principles of diversification, lack of control and authorship as references for a socio-cultural action that will stimulate citizenship training. This is based on making the protagonists "do useful things" in local scenarios that offer the opportunity for improvement, on promoting actions that will encourage self-reflection, and on raising awareness about the complexity of reality itself. These are principles that can be applied in educational experiences throughout people's life spans from their beginnings.